Stability of polyelectrolyte multilayers in oxidizing media: a critical issue for the development of multilayer based membranes for nanofiltration - Gregurec, Danijela; Olszyna, Mateusz; Politakos, Nikolaos; Yate, Luis; Dahne, Lars; Moya, Sergio Enrique (Colloid and Polymer Science, 2014)
Polyelectrolyte multilayers (PEMs) for nanofiltration and reverse osmosis are fabricated by means of the Layer by Layer technique from the negatively charged poly(sodium 4-styrenesulfonate) (PSS) and polycations with primary, secondary, tertiary, and quaternary amines. PEMs stability is studied after treatment with the oxidizing agent sodium hypochlorite (NaOCl), in the same conditions as in membrane modulus cleaning. PEM assembly and mass changes after treatment with NaOCl are studied with the Quartz Crystal Microbalance. The chemical composition of the PEMs after the treatment with NaOCl is studied by X-ray photoelectron spectroscopy. The oxidation of polycations in bulk is studied by UV–vis. The PEMs fabricated with poly(diallydimethylammonium chloride) (PDADMAC) and poly(vinylbenzyltrimethylammonium chloride) (PVBTMAC), bearing quaternary amines, show the highest chemical stability and smallest mass variations after oxidation. PEMs including other polycations bearing quaternary amines and polycations with primary, secondary, and tertiary amines are either fully removed or significantly changed chemically.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Oxidation; Polyelectrolyte multilayer; QCM-D; XPS